Short-term plyometric training improves altered neuromotor control during running after cycling in triathletes - Bonacci, J.; Green, D.; Saunders, P.; Franettovich, M.; Chapman, A.; Blanch, P.; Vicenzino, B. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Cycling has a direct negative effect on some highly-trained triathletes' ability to execute optimal neuromotor strategies specific to running (Chapman et al., 2008). The presence of altered neuromotor control when running off-the-bike has been associated with exercise-related leg pain (Chapman et al., 2010). Accordingly, identification of training interventions that could minimise this interference may aid in prevention of injury and augmentation of performance during running following cycling. Plyometric training is a specific form of strength training that has been reported to improve running economy by enhancing neuromuscular function (Paavolainen et al., 1999). The primary aim of this study was to examine the effect of plyometric training on triathletes neuromotor control and running economy in those in which neuromotor control is aberrant during running after cycling.